A construção de consenso em reuniões do conselho escolar: contribuições da linguística da enunciação e da ergologia para entender a atividade de trabalho do gestor - Messa, Rosângela Markmann (Universidade do Vale do Rio dos Sinos, 2015)
This thesis investigates, based on Emile Benveniste’s enunciative theory and on Yves Schwartz’s ergologic perspective, the consensus formation process in School Board meetings of an Evangelical Lutheran School, located in Porto Alegre metropolitan area. From the Benveniste’s enunciation theory, it is used the conception of language, in which language provides a formal basis system from which the individual takes the language act, renormalizing it in a particular and unique style. From the ergologic perspective, it is used the concept of work activity, which shows that there is always a distance between the foregoing provisions governing the work to be done, and the work actually done. Hence work is made unique and renormalized constantly as the work activities are carried out. Both theories take into consideration the subjectivity which is inherent to language and work activity. The research is qualitative in nature and has dialogues among the principal, the administrative coordinator and members of the School Board as the object of study. From the analysis of the dialogues, it is possible to state that consensus is co-constructed by the participants in the interaction; it is created by taking into consideration the establishment of an "I" and a "you", who speak of a "he", in a specific here and now; it is the result of a process which extends over time, induced by the institution and people who reproduce it, in which different participants perform specific activities related to their role, and thereby overcome logical and necessary development steps within the actions required from them.
Keywords: Ergologia; Enunciação; Gestão escolar; Escolas evangélico-luteranas; Consenso; Ergology; Enunciation; School management; Evangelical lutheran schools; Consensus; ACCNPQ::Lingüística, Letras e Artes::Lingüística